Deciphering the role of IGFBP5 in delaying fibrosis and sarcopenia in aging skeletal muscle: therapeutic implications and molecular mechanisms - Shi, Luze; Ding, Zheci; Chen, Jiwu (Frontiers in Pharmacology, 2025)
IntroductionSarcopenia is a condition characterized by the loss of muscle fibers and excessive deposition of extracellular matrix proteins. The interplay between muscle atrophy and fibrosis is a central feature of sarcopenia. While the mechanisms underlying skeletal muscle aging and fibrosis remain incompletely understood, cellular senescence has emerged as a key contributor. This study investigates the role of D-galactose (D-gal) in inducing fibroblasts senescence and skeletal muscle fibrosis, and aims to find the key regulator of the process to serve as a therapeutical target.MethodsTo discover the role of D-gal in inducing cellular senescence and fibrosis, the senescence markers and the expression of fibrosis-related proteins were assessed after introducing D-gal among fibroblasts, and muscle strength and mass. The severity of muscle atrophy and fibrosis were also verified by using H&E staining and Masson trichrome staining after D-gal treatment via subcutaneous injection among mice. Subsequently, mRNA sequencing (RNA-seq) was performed and the differential expressed genes were identified between under D-gal or control treatment, to discover the key regulator of D-GAL-driven fibroblasts senescence and fibrosis. The role of the key regulator IGFBP5 were then validated in D-GAL treated IGFBP5-knockdown fibroblasts in vitro by analyzing the level of senescence and fibrosis-related markers. And the results were further confirmed in vivo in IGFBP5-knockdown SAMP8 mice with histological examinations.ResultsD-gal treatment effectively induced cellular senescence and fibrosis in fibroblasts, as well as skeletal muscle atrophy, fibrosis and loss in muscle mass and function in mice. IGFBP5 was identified as a key regulator of D-GAL induced senescence and fibrosis among fibroblasts using RNA-seq. And further validation tests showed that IGFBP5-knockdown could alleviate D-GAL-induced fibroblast cellular senescence and fibrosis, as well as the severity of muscle atrophy and fibrosis in SAMP8 mice.DiscussionIGFBP5 emerging as a key regulator of D-GAL-induced fibroblast cellular senescence and fibrosis. The findings provide new insights into the molecular mechanisms underlying age-related skeletal muscle fibrosis and highlight IGFBP5 as a potential therapeutic target. Further research is needed to validate these findings and explore related clinical applications.